2014
DOI: 10.1371/journal.pone.0104027
|View full text |Cite
|
Sign up to set email alerts
|

Improving Maternal and Newborn Health: Effectiveness of a Community Health Worker Program in Rural Kenya

Abstract: BackgroundVolunteer community health workers (CHWs) form an important element of many health systems, and in Kenya these volunteers are the foundation for promoting behavior change through health education, earlier case identification, and timely referral to trained health care providers. This study examines the effectiveness of a community health worker project conducted in rural Kenya that sought to promote improved knowledge of maternal newborn health and to increase deliveries under skilled attendance.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 17 publications
5
74
0
6
Order By: Relevance
“…The study results confirm the importance of community interventions in promoting birth preparedness and knowledge of obstetric danger signs in rural communities [10,25]. The study results also indicate existing gaps in birth preparedness practice in rural communities.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The study results confirm the importance of community interventions in promoting birth preparedness and knowledge of obstetric danger signs in rural communities [10,25]. The study results also indicate existing gaps in birth preparedness practice in rural communities.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, the interaction between study area and VHT home visits indicated that the odds of obstetric danger signs’ knowledge and birth preparedness were higher among intervention residents who were visited by the VHTs. Other studies have also indicated the importance of community health workers in improving the knowledge of obstetric danger signs as well as birth preparedness among women [25,29,30]. …”
Section: Discussionmentioning
confidence: 99%
“…Other authors have emphasized the scope of the intervention, implementation efficiency, availability of resources, leadership and local contextual issues as key factors that influence the successful implementation of interventions [6,28]. Local contextual cultural factors were noted to be vital in changing newborn care practices.…”
Section: Discussionmentioning
confidence: 99%
“…Community-based strategies that involve the training of CHWs and traditional birth attendants have resulted in increased awareness of maternal and newborn health and newborn danger signs, increased utilization of antenatal care (ANC) and facility delivery [1,17,20,27,28], and increased newborn care practices such as clean cord care, immediate breastfeeding, thermal care and delayed bathing [19,21]. Community mobilization and the use of community support groups have also resulted in increased awareness and knowledge about maternal and newborn health and increased facility deliveries [6].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, given the limited human resources in the health sector, a community-based approach has been promoted as a cost-effective and pro-poor intervention to improve the accessibility of health care [5, 6]. Community health workers (CHWs) are often employed as a key element of the community-based approach to the rural population of low- and middle-income countries [7].…”
Section: Introductionmentioning
confidence: 99%